Diseases of the Abdomen and Pelvis 2018-2021 Diagnostic Imaging - IDKD Book (IDKD Springer Series,, 2018)
This open access book deals with imaging of the abdomen and pelvis, an area that has seen considerable advances over the past several years, driven by clinical as well as technological developments. The respective chapters, written by internationally respected experts in their fields, focus on imaging diagnosis and interventional therapies in abdominal and pelvic disease; they cover all relevant imaging modalities, including magnetic resonance imaging, computed tomography, and positron emission tomography. As such, the book offers a comprehensive review of the state of the art in imaging of the abdomen and pelvis. It will be of interest to general radiologists, radiology residents, interventional radiologists, and clinicians from other specialties who want to update their knowledge in this area.